The Influence of Transformational Leadership on the Effectiveness of Decision Making in Startup Companies in Surabaya - Firmansyah, M. Fahmi; Suryanto, Dhia Aulia; Putri, Felicia Aurelia; Sihite, Julius Emmanuel; Hidayat, Rusdi; Respati K, Indah (Indonesian Journal of Public Administration Review, 2025)
The focus of this study is to see how leadership affects how effective teamwork decision-making is. Effective leadership is essential to achieving common goals in dynamic and competitive organizations. This study uses a descriptive-correlational approach and a quantitative survey. Respondents are work teams from various organizations. The results of the study indicate that participative leadership style affects decision quality, time efficiency, and team satisfaction. Leaders who are able to communicate well, manage conflict, and set clear goals have the ability to create an environment that encourages creativity and cooperation. To improve the decision-making process in work teams, this study suggests a more participative leadership style and improved communication skills.